Salidroside may target PPARα to exert preventive and therapeutic activities on NASH - Chu, Xueru; Liu, Shousheng; Qu, Baozhen; Xin, Yongning; Lu, Linlin (Frontiers in Pharmacology, 2024)
Background Salidroside (SDS), a phenylpropanoid glycoside, is an antioxidant component isolated from the traditional Chinese medicine Rhodiola rosea and has multifunctional bioactivities, particularly possessing potent hepatoprotective function. Non-alcoholic steatohepatitis (NASH) is one of the most prevalent chronic liver diseases worldwide, but it still lacks efficient drugs. This study aimed to assess the preventive and therapeutic effects of SDS on NASH and its underlying mechanisms in a mouse model subjected to a methionine- and choline-deficient (MCD) diet. Methods C57BL/6J mice were fed an MCD diet to induce NASH. During or after the formation of the MCD-induced NASH model, SDS (24 mg/kg/day) was supplied as a form of diet for 4 weeks. The histopathological changes were evaluated by H&E staining. Oil Red O staining and Sirius Red staining were used to quantitatively determine the lipid accumulation and collagen fibers in the liver. Serum lipid and liver enzyme levels were measured. The morphology of autophagic vesicles and autophagosomes was observed by transmission electron microscopy (TEM), and qRT-PCR and Western blotting were used to detect autophagy-related factor levels. Immunohistochemistry and TUNEL staining were used to evaluate the apoptosis of liver tissues. Flow cytometry was used to detect the composition of immune cells. ELISA was used to evaluate the expression of serum inflammatory factors. Transcript–proteome sequencing, molecular docking, qRT-PCR, and Western blotting were performed to explore the mechanism and target of SDS in NASH. Results The oral administration of SDS demonstrated comprehensive efficacy in NASH. SDS showed both promising preventive and therapeutic effects on NASH in vivo. SDS could upregulate autophagy, downregulate apoptosis, rebalance immunity, and alleviate inflammation to exert anti-NASH properties. Finally, the results of transcript–proteome sequencing, molecular docking evaluation, and experimental validation showed that SDS might exert its multiple effects through targeting PPARα. Conclusion Our findings revealed that SDS could regulate liver autophagy and apoptosis, regulating both innate immunity and adaptive immunity and alleviating inflammation in NASH prevention and therapy via the PPAR pathway, suggesting that SDS could be a potential anti-NASH drug in the future.